Megatrends and the future of African economies - Traub, Lulama; Yeboah, Felix K.; Meyer, Ferdinand; Jayne, Thomas S. (International Food Policy Research Institute, 2015)
This article argues that these projections about Africa’s future are a good deal less certain than the conventional wisdom might suggest. Foresighting exercises are often based on tenuous evidence of key underlying trends and tenuous assumptions about the degree to which these trends are inevitable exogenous forces. Most current trends are neither irreversible nor inevitable. Just as the current trends being observed in African food systems are the outcomes of the policies and public investment patterns of prior decades, the future will be shaped and transformed by today’s policy actions—either those taken proactively or those taken passively as a result of no action (Seidman 1973). This point may be underappreciated by development thinkers who speak in terms of inevitable transformations